Analisis Survival terhadap Kekambuhan Pasien Penderita Asma menggunakan Pendekatan Counting Process: (Studi Kasus: Balai Besar Kesehatan Paru Masyarakat Makassar) - Abdy, Muhammad; Sanusi, Wahidah; Aulia, Hikma (Journal of Mathematics, Computations and Statistics, 2022)
Survival analysis or survival analysis is a set of statistical procedures to analyze data with the time until a particular event occurs as a response variable. Observe events such as death and recurrence of the disease. Survival analysis used for recurring data is the counting process approach for identic and stratified cox recursion events for non-identical recursion events. An example of identic recursion data is patient recurrence data of non-communicable diseases such as asthma. The type of research carried out is applied research with a quantitative approach, namely by taking or collecting the necessary data and analyzing it using the counting process approach method. The counting process approach method is a specific method used for identical reccuring event, each recurring event will be counted as a new and independent event. The variables used in the study were Time, Status, Gender, Age, Smoker, Allergies, Obesity, and Atopic History. Based on the results of this study, it was found that the factors of gender, age, and atopic history had an effect on the recurrence of asthmatic patients with a significance level of less than 10%.